Becoming (un)employed and life satisfaction: Asymmetric effects and potential omitted variable bias in empirical happiness studies - Wolfgang Maennig; Markus Wilhelm (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2011)
Becoming unemployed has negative effects on life satisfaction; a transition from unemployment to employment, however, has only small positive effects. This asymmetry indicates a potential omitted variable bias in previous empirical happiness studies, with the consequence of underesti-mated effects of unemployment on life satisfaction. There are also gender-specific effects of asymmetry.
Keywords: I31; J01; Z13; 330; Happiness; life satisfaction; asymmetric effect; labour status; employment; unemployment